A theory of musical semiotics - Tarasti, Eero.; Indiana University. Press (Bloomington : Indiana University Press, 1994)
Eero Tarasti advances a semiotic theory of music based on information provided by the history of Western music and by various sign theories. A Theory of Musical Semiotics is at the same time a study of music as a narrative art. It analyzes musical works through the theoretical frameworks of narratology and French structural semiotics, especially that of A. J. Greimas. Tarasti views other theories from the "classical" semiotic tradition, from Saussure to Peirce to Lotman, as possible foundations of musical semiotics. A Theory of Musical Semiotics provides a model for the semiotic analysis of both musical structure and semantics. It introduces the English-language reader to musical narratology, a field of inquiry that until recently has remained largely the province of European researchers.
Contents r t t t t t t t t t
Includes bibliographical references (pages [313]-323) and index.
Keywords: Music -- Semiotics; Music theory; Musical analysis